Innovative retargeted oncolytic herpesvirus against nectin4-positive cancers - Vannini, Andrea; Parenti, Federico; Forghieri, Cristina; Barboni, Catia; Zaghini, Anna; Campadelli-Fiume, Gabriella; Gianni, Tatiana (Frontiers in Molecular Biosciences, 2023)
Nectin4 is a recently discovered tumor associated antigen expressed in cancers that constitute relevant unmet clinical needs, including the undruggable triple negative breast cancer, pancreatic ductal carcinoma, bladder/urothelial cancer, cervical cancer, lung carcinoma and melanoma. So far, only one nectin4-specific drug—Enfortumab Vedotin—has been approved and the clinical trials that test novel therapeutics are only five. Here we engineered R-421, an innovative retargeted onco-immunotherapeutic herpesvirus highly specific for nectin4 and unable to infect through the natural herpes receptors, nectin1 or herpesvirus entry mediator. In vitro, R-421 infected and killed human nectin4-positive malignant cells and spared normal cells, e.g., human fibroblasts. Importantly from a safety viewpoint, R-421 failed to infect malignant cells that do not harbor nectin4 gene amplification/overexpression, whose expression level was moderate-to-low. In essence, there was a net threshold value below which cells were spared from infection, irrespective of whether they were malignant or normal; the only cells that R-421 targeted were the malignant overexpressing ones. In vivo, R-421 decreased or abolished the growth of murine tumors made transgenic for human nectin4 and conferred sensitivity to immune checkpoint inhibitors in combination therapies. Its efficacy was augmented by the cyclophosphamide immunomodulator and decreased by depletion of CD8-positive lymphocytes, arguing that it was in part T cell-mediated. R-421 elicited in-situ vaccination that protected from distant challenge tumors. This study provides proof-of-principle specificity and efficacy data justifying nectin4-retargeted onco-immunotherapeutic herpesvirus as an innovative approach against a number of difficult-to-drug clinical indications.